#122 A Molecular docking study for antiasthmatic targets of Manilkara zapota (L.) P. Royen leaves in treating asthma - Agrawal, Mansi; Mazumder, Papiya MItra (Journal of Pharmaceutical Chemistry, 2022)
Asthma is a chronic reversible allergic inflammatory disease of lung airways that affects millions of people worldwide; even then, only symptomatic treatment is given to control asthma. At present, the low dose inhaled corticosteroids are the standard gold treatment for asthma but have many severe side effects. So, this study aimed to search for a natural potent anti-inflammatory therapeutic agent that reverses this inflammatory disease with fewer side effects. In this, Manilkara zapota (L.) P. Royen is a medicinal plant, majorly rich in polyphenols. All the more, leaves of Manilkara zapota (L.) In traditional medical practice, Manilkara zapota (L.) P. Royen has been used to treat diseases like fever, hemorrhage, cough, and cold. In addition, previous pharmacological studies have found antioxidant, anti-inflammatory, antitumor, and antiarthritis bioactive properties. Still, no scientific data is available regarding the antiasthmatic profile of the leaves of Manilkara zapota (L.) P. Royen. In this study, phytoconstituents rich in polyphenols present in Manilkara zapota (L.) P. Royen leaves were docked with different asthmatic targets like ß-2 adrenergic receptor (PDB ID: 2RH1), leukotriene receptor (PDB ID: 6RZ6), NFк-B receptor (PDB ID: 1A3Q) via software AutoDock Vina 1.1.2. Molecular docking results revealed that Apigenin-7-rhamnoside exhibited a high affinity of -8.2 kcal/mol for the ß-2 adrenergic receptor (PDB ID: 2RH1) selected target among the studied compounds compared to standard control Formoterol with binding energy -6.4 kcal/mol. Thus, Apigenin7-rhamnoside, a flavonoid, is present in Manilkara zapota (L.) P. Royen leaves could be predicted possible as a bronchodilator agent for treating asthma. Therefore, in this experiment, an attempt was made to identify a natural potent antiasthmatic agent with the help of molecular docking, if validated in the wet lab, which could be used to treat asthma with less severe adverse effects.